Antagonistic Regulation of CFTR Cell Surface Expression by Protein Kinases WNK4 and Spleen Tyrosine Kinase - Mendes, A.I. (2011)
Members of the WNK (with no lysine (K)) subfamily of protein kinases regulate various ion channels involved in sodium, potassium and chloride homeostasis by either inducing their phosphorylation or regulating the number of channel proteins expressed at the cell surface. Here, we describe that WNK4 promotes the cell surface expression of the cystic fibrosis transmembrane conductance regulator (CFTR) in mammalian cells. The mechanism by which WNK4 acts on CFTR involves interaction with spleen tyrosine kinase (Syk), which we find to phosphorylate Tyr512 in the first nucleotide-binding domain (NBD) 1 of CFTR. The presence of WNK4 prevents the phosphorylation of NBD1 by Syk in vitro in a kinase-independent manner. In baby hamster kidney cells stably expressing CFTR, catalytically active Syk reduces while WNK4 promotes the cell surface expression of CFTR. This is shown by biotinylation of cell surface proteins, immunofluorescence microscopy and functional efflux assays. Mutation of Tyr512 to either glutamic acid or phenylalanine is sufficient to alter CFTR surface levels. Together, our results identify that Tyr512 phosphorylation is a novel signal regulating the prevalence of CFTR at the cell surface and describe an antagonistic role of WNK4 and Syk in this process.